Nexus between CO2 emission, energy consumption and economic growth in ASEAN countries plus China - Mustafa, Ghulam; Abd Latif, Ismail; Shah, Said Zamin; Bashir, Muhammad Khalid (Science Publications, 2016)
This study mainly contributes to test the Environmental Kuznets Curve (EKC) hypothesis using panel data for the ASEAN (Malaysia, Indonesia, Thailand and Philippines) countries plus China. Empirical focus of the study is to examine the nexus between CO2 emission, energy consumption and economic growth. While using panel data for 1971-2008 and applying panel co-integration techniques, the emergent findings of the study showed a positive relationship between per capita GDP and per capita CO2 emission. Further, we found positive effect of energy consumption on CO2 emission in long run. However, the study findings confirmed EKC inverted U-shape hypothesis for the ASEAN-china region after the inclusion of energy consumption. However, it did not hold once only quadratic relationship of per capita income was regressed with CO2 emission. Our long-run Panel Ordinary Least Squares (POLS), Dynamic Ordinary Least Squares (DOLS) and Fully Modified Ordinary Least Squares (FMOLS) estimates also confirmed U-shaped EKC hypothesis for this sample of ASEAN4 countries plus China. The findings of the study suggest the countries under consideration should focus on increasing per capita income to sustain long term economic growth and to reduce pollutants and hence, CO2 emission in the region.